2019
DOI: 10.1108/caer-08-2018-0170
|View full text |Cite
|
Sign up to set email alerts
|

What are the driving factors of pesticide overuse in vegetable production? Evidence from Chinese farmers

Abstract: Purpose Pesticide overuse has caused a series of negative impacts on environment and human health. The purpose of this paper is to examine the farmers’ behavior of pesticide overuse and to identify the underlying determinants, based on the survey data from Shandong Province, China. Design/methodology/approach A two-stage semiparametric approach and the binary probit model were employed in this study to analyze the marginal pesticide productivity and investigate the determinants of the pesticide overuse. Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 32 publications
0
41
0
Order By: Relevance
“…Furthermore, a European scale study by Geiger et al (2010) showed that local pesticide application had persistent negative effects on biological pest control. found that increasing pesticide use decreased removal rates of moth eggs in vineyards, and Yang et al (2019) conclude that ladybeetle abundance in wheat fields decreased with increasing insecticide use at the local scale. The combination of negative effects of pesticides on-field, but no effects off-field, could imply that in landscapes with high land-use intensities (e.g.…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“…Furthermore, a European scale study by Geiger et al (2010) showed that local pesticide application had persistent negative effects on biological pest control. found that increasing pesticide use decreased removal rates of moth eggs in vineyards, and Yang et al (2019) conclude that ladybeetle abundance in wheat fields decreased with increasing insecticide use at the local scale. The combination of negative effects of pesticides on-field, but no effects off-field, could imply that in landscapes with high land-use intensities (e.g.…”
Section: Discussionmentioning
confidence: 89%
“…There are several studies that report on interactions between pesticide use and landscape factors. Yang et al (2019) found that beneficial insect abundance were low in areas with a frequent insecticide sprays, regardless of the landscape context, while Ricci et al (2019) reported that negative effects of local pesticide use intensity on beneficial insects was only sometimes modified by landscape characteristics. Gagic et al (2019) showed that the recovery time of natural enemies after insecticide spraying in cotton fields was not compensated for by the presence of semi-natural field margins.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations